Molecular characterization of Oryza sativa WRKY6, which binds to W‐box‐like element 1 of the Oryza sativa pathogenesis‐related (PR) 10a promoter and confers reduced susceptibility to pathogens. Issue 3 (17th June 2015) - Choi, Changhyun; Hwang, Seon‐Hee; Fang, Il Ran; Kwon, Soon Il; Park, Sang Ryeol; Ahn, Ilpyung; Kim, Jung Bong; Hwang, Duk‐Ju
Summary WRKY proteins are transcription factors (TFs) that regulate the expression of defense‐related genes. The salicylic acid (SA)‐inducible Oryza sativa WRKY6 (OsWRKY6) was identified as a positive regulator of Oryza sativa pathogenesis‐related 10a (OsPR10a) by transient expression assays. A physical interaction between OsWRKY6 and W‐box‐like element 1 (WLE1), which positively regulates OsPR10a/probenazole induced protein 1 expression, was verified in vitro. Several pathogenesis‐related (PR) genes were constitutively activated, including OsPR10a, and transgenic rice (Oryza sativa) plants overexpressing (ox) OsWRKY6 exhibited enhanced disease resistance to pathogens. By contrast, PR gene induction was compromised in transgenic OsWRKY6‐RNAi lines, suggesting that OsWRKY6 is a positive regulator of defense responses. OsWRKY6‐ox lines displayed leaf lesions, and increased OsWRKY6 levels caused cell death. Salicylic acid (SA) concentrations were higher in OsWRKY6‐ox lines than in wild‐type (WT) plants, and transcript levels of Oryza sativa isochorismate synthase 1 (OsICS1), which encodes a major enzyme involved in SA biosynthesis, were higher in OsWRKY6‐ox lines than in WT. OsWRKY6 directly bound to the OsICS1 promoter in vivo. This indicates that OsWRKY6 can directly regulate OsICS1 expression and thereby increase SA concentrations. OsWRKY6 autoregulates its own expression. OsWRKY6 protein degradation is possibly regulated by ubiquitination. Our results suggest that OsWRKY6 positively regulates defense responses through activation of OsICS1 expression and OsWRKY6 stabilization.